Exosomally derived Y RNA fragment alleviates hypertrophic cardiomyopathy in transgenic mice - Feng Huang; Na Na; Takeshi Ijichi; Xiaokang Wu; Kazutaka Miyamoto; Alessandra Ciullo; My Tran; Liang Li; Ahmed Ibrahim; Eduardo Marbán; Geoffrey de Couto (Elsevier, 2021)
Cardiosphere-derived cell exosomes (CDCexo) and YF1, a CDCexo-derived non-coding RNA, elicit therapeutic bioactivity in models of myocardial infarction and hypertensive hypertrophy. Here we tested the hypothesis that YF1, a 56-nucleotide Y RNA fragment, could alleviate cardiomyocyte hypertrophy, inflammation, and fibrosis associated with hypertrophic cardiomyopathy (HCM) in transgenic mice harboring a clinically relevant mutation in cardiac troponin I (cTnIGly146). By quantitative PCR, YF1 was detectable in bone marrow, spleen, liver, and heart 30 min after intravenous (i.v.) infusion. For efficacy studies, mice were randomly allocated to receive i.v. YF1 or vehicle, monitored for ambulatory and cardiac function, and sacrificed at 4 weeks. YF1 (but not vehicle) improved ambulation and reduced cardiac hypertrophy and fibrosis. In parallel, peripheral mobilization of neutrophils and proinflammatory monocytes was decreased, and fewer macrophages infiltrated the heart. RNA-sequencing of macrophages revealed that YF1 confers substantive and broad changes in gene expression, modulating pathways associated with immunological disease and inflammatory responses. Together, these data demonstrate that YF1 can reverse hypertrophic and fibrotic signaling pathways associated with HCM, while improving function, raising the prospect that YF1 may be a viable novel therapeutic candidate for HCM.